2018
DOI: 10.1007/s11356-018-3243-0
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme activity modification in adult beetles (Agelastica coerulea) inhabiting birch trees in an ozone-enriched atmosphere

Abstract: Tropospheric ozone (O 3) is a naturally occurring gas in the atmosphere. However, the concentration of O 3 increased in the 20 th century. Although the effects of O 3 on vegetation have been extensively studied since the 1950s, limited information exists regarding the effects of O 3 on insect herbivores. In particular, evidence is lacking regarding the effects of O 3 on the biology of insect herbivores. Agelastica coerulea (Baly, 1874) is a coleopteran species that grazes on Betulaceae plants. In this study, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…In fact, an analysis of the results of over 200 published studies suggested that leaf feeders can perform better on host plants that are stressed than on plants that are nonstressed, in support to the plant vigor hypothesis (Galway et al, 2004). In agreement to these, adult beetles of a different species (Agelastica coerulea) inhabiting birch trees in this FACE system were found to have higher activities of total antioxidants and lower detoxifying hydrolase such as α-and β-esterases in EOZ than in AOZ, although direct EOZ impacts on insects and indirect effects via plants cannot be separated (ElEla et al, 2018). Similarly to O3, leaf number with oviposited eggs was not affected by N despite there was a lower number of insects on N50 plants than on N0 plants on 20 July and September 19.…”
Section: Plant and Insect Responses To Ozone Exposuresupporting
confidence: 70%
See 1 more Smart Citation
“…In fact, an analysis of the results of over 200 published studies suggested that leaf feeders can perform better on host plants that are stressed than on plants that are nonstressed, in support to the plant vigor hypothesis (Galway et al, 2004). In agreement to these, adult beetles of a different species (Agelastica coerulea) inhabiting birch trees in this FACE system were found to have higher activities of total antioxidants and lower detoxifying hydrolase such as α-and β-esterases in EOZ than in AOZ, although direct EOZ impacts on insects and indirect effects via plants cannot be separated (ElEla et al, 2018). Similarly to O3, leaf number with oviposited eggs was not affected by N despite there was a lower number of insects on N50 plants than on N0 plants on 20 July and September 19.…”
Section: Plant and Insect Responses To Ozone Exposuresupporting
confidence: 70%
“…These may relate to changing insect damages induced by environmental changes (Santini et al 2004;Santini and Faccoli 2015), especially N deposition and O3 that can change plant-insect interaction and consequently contribute in the decline of forest trees (Koike et al 2013;Koike 2016). Only three studies have evaluated the leaf defense capacity of Japanese trees in relation to insect dynamics in free-air O3-concentration enrichment (FACE) systems (Sakikawa et al 2016;Agathokleous et al 2017a;ElEla et al 2018), and none of them concerns Japanese elm, despite previous researches have reported that grazing activities of elm leaf beetles was increased by elevated O3 (Richard et al 1988;Barger et al 1992).…”
Section: Introductionmentioning
confidence: 99%
“…White birch, a common species in forests and often grown as boulevard in cities of Hokkaido in Japan [10,11,13], has heterophyllous leaves known as early and late leaves. Early leaves expand from the beginning of May, while late leaves start to develop after complete expansion of early leaves from around mid-July in northern Japan [24].…”
Section: Plant Materialsmentioning
confidence: 99%
“…Damages by herbivores are responsible for losses of net primary production up to 15% in temperate forests [8]; however, herbivory can be altered by atmospheric contaminants. For example, we have previously found that insect herbivores systematically grazed leaves of different tree species in ambient O 3 plots more than in elevated O 3 plots of a free-air O 3 -concentration enrichment (FACE) system [10][11][12]. However, even if, in that situation, the leaves in the elevated O 3 condition had lower chemical defense capacities [12,13], leaves from the elevated O 3 conditions were often preferred by insects in choice laboratory assays [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation